Motivation factors for beef processor-producer linkages - J.D. Lawrence; M.L. Hayenga; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2001)
A survey was conducted of the 15 largest beef processors to identify the mix of procurement practices being used and to understand reasons motivating recent processorproducer linkages. Processors are shifting away from cash-market live, fed-cattle trade, which represents only 36% of cattle procured by survey respondents in 1999. Processorowned cattle feeding represents only approximately 5%, where it has been for more than a decade. Various other forms of pricing such as carcass weight, grid, and formula represented the largest portion of purchases at 49%. Processors indicated the two most important reasons they get involved in contracts and marketing agreements with producers is to secure higher and more consistent quality cattle. Assuring food safety was also a motivation for linking more closely with cattle producers. In the future, processors felt these motivational factors would increase in importance. As cattle feeders explore grid pricing and alliance opportunities, it is important they understand why processors desire to enter into contracts and marketing agreements.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Beef processors; Contracts; Marketing agreements; Cattle marketing